If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 11 = 2(46) + 11 Reorder the terms: 11 + 2x = 2(46) + 11 Multiply 2 * 46 11 + 2x = 92 + 11 Combine like terms: 92 + 11 = 103 11 + 2x = 103 Solving 11 + 2x = 103 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 2x = 103 + -11 Combine like terms: 11 + -11 = 0 0 + 2x = 103 + -11 2x = 103 + -11 Combine like terms: 103 + -11 = 92 2x = 92 Divide each side by '2'. x = 46 Simplifying x = 46
| 3(x-6)-6(x-3)=x+3-2(x-3) | | 8=9x+6 | | 20+-1x= | | C(x)=x^2-40x+405 | | Y-2y-3y-6=0 | | .05c=.08+7.50 | | x+5=5x+25 | | y-(-5)=-6(x-1) | | 2x-71.50=4308.50 | | x+(x+5)+(2x+11)=180 | | 3/4y-6=0 | | x-20+x= | | 695=13(k+5)+32 | | logx=0.45 | | 7b=85 | | 10(g-836)=740 | | 5x-5(-6-2x)=0 | | 5-7x=2x+8 | | 2-2y-3y=0 | | 9x-(3x+3)=4x-49 | | -2=6-x | | 29=2+3g | | 8(4w+9)=-8 | | 4x^2-11x+15=0 | | 9r+8s-5(8r-5s)= | | 3x^2+12x-24=-26 | | 1/3x^2-1/12x-1/6=0 | | 803=792-b | | -6(q-81)=-30 | | 4.3(4+2x)-4.2=13 | | 2(8x+4)=22x | | -10(s+5)=-101 |